Aircraft ground movement delay: a descriptive statistical analysis at Kuala Lumpur International Airport - Izuddin Md. Ithnan, M. (IEOM Society, 2016)
Delay commonly used in classifying the level of service (LOS) hence indicating the traffic performance of a road segment. For aircraft ground movement, delay contributes directly to the increasing of operational cost, accident possibility, noise pollution and ground emission. In this study, Kuala Lumpur International Airport, KLIA airside configuration was marked as nodes in Google Earth®. Ground movement of each aircraft from nodes to nodes is recorded based on the aircraft transponder signal. The Database was then analyzed using MySQL via Cygwin64 interface. A detail preliminary descriptive statistical analysis was carried out to get more insight of the current airside ground logistic performance and furthermore determine the delay patterns and characteristics. This result is crucial for future research of optimizing aircraft airside ground movement particularly at KLIA.